Analisis Framing Berita Pemilu Capres 2024 di Media Liputan6.com - Afifah, nur; Erwan Efendi (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The purpose of this study is to investigate how social media is used in political contexts, particularly during the Indonesian presidential election of 2024. Social media has grown in importance in people's daily lives in the modern digital age, especially in the political sphere. A notable instance of presidential contenders using social media deliberately to sway voters is the Indonesian presidential election of 2024. Using a qualitative technique and a descriptive research design, this study focuses on the three leading candidates for the presidency of Indonesia in 2024. The data analysis technique used by the researchers is framing analysis. The goal of framing analysis is to ascertain how a media outlet manages the framing of news about, in this case, the Indonesian presidential candidates for 2024. The researchers discover that the media frequently gives more coverage to the front-runner for president after looking at a variety of presidential election stories. The real count results, which show one candidate ahead of the others, clearly demonstrate this. The research's conclusions offer a clearer knowledge of the political application of social media as well as how it affects the public's perception and attitude toward presidential candidates. Additionally, this study provides campaign teams and presidential candidates with information into how important social media tactics are in shaping public opinion.